HexSimProcessor - Gong,H; Wenjun,G; Neil,M (2020)
This repository is for the publication: "GPU-accelerated real-time reconstruction in Python of three-dimensional datasets from structured illumination microscopy with hexagonal patterns". It includes: raw data from experiments and simulations, the code for generating the simulated data, and the code for post-processing the raw data.